Independent Associations With 30- and 90-Day Unplanned Readmissions After Elective Lumbar Spine Surgery: A National Trend Analysis of 144 123 Patients. Issue 3 (11th June 2018) - Elsamadicy, Aladine A; Ren, Xinru; Kemeny, Hanna; Charalambous, Lefko; Sergesketter, Amanda R; Rahimpour, Shervin; Williamson, Theresa; Goodwin, C Rory; Abd-El-Barr, Muhammad M; Gottfried, Oren N; Xie, Jichun; Lad, Shivanand P
Abstract: BACKGROUND: Unplanned hospital readmissions contribute significantly to soaring national healthcare expenditures. To alleviate this burden, Centers for Medicare and Medicaid Services implemented initiatives to penalize hospitals for unplanned 30-d hospital readmissions. There is a paucity of data identifying patient risk factors independently associated with 30- and 90-d readmissions. OBJECTIVE: To investigate similarities in patient risk factors associated with 30- and 90-d unplanned readmissions following elective lumbar spine surgery. METHODS: The National Readmission Database (NRD) was queried to identify patients undergoing elective lumbar spine surgery between 2013 and 2014. Patients were grouped by no readmission (Non-R), unplanned readmission within 30 days (30-R), and unplanned readmission within 31 to 90 days (90-R). Multivariate analysis determined factors associated with 30- and 90-d readmissions. RESULTS: We identified 144 123 patients with 10 592 (7.3%) patients experiencing an unplanned readmission (30-R: n = 7228 [5.0%]; 90-R: n = 3364 [2.3%]; Non-R: n = 133 531). The most common inpatient complication observed in those patients readmitted was dural tear (30-R: 7.7%, 90-R: 4.6%, Non-R: 4.3%). The most prevalent 30- and 90-d complication seen among the readmitted cohort was infection (30-R: 18.5%, 90-R: 7.4%). In multivariate regression analysis, age, insurance status, chronic obstructive pulmonary disorder (COPD), depression, hypertension, diabetes, deficiency anemia, and obesity were independently associated with 30-d readmission; however, age and obesity were not independently associated with 90-d readmission. CONCLUSION: Our study demonstrated national unplanned readmission rates after elective spinal surgery to be 7.3%. With age, insurance status, COPD, depression, hypertension, diabetes, deficiency anemia, obesity, and depression all independently associated with unplanned hospital readmission. Future solutions that focus on reducing preventable readmissions may improve patient outcomes and reduce healthcare costs.